Integrated anthropo-technogenic pressures on urban territories of some of large industrial cities and federal resorts of Russian Federation - I. S. Pomelyayko; V. I. Pomelyayko (Известия высших учебных заведений: Геология и разведка)
The assessment of the total impact of environmental factors on the health of the population in 30 cities of Russia is estimated. The evaluation was performed on the largest integrated anthropotechnogenic impact on the environment. Summary indicators of air pollution, water and groundwater for cities with tense and critical ecological state (ES) (categories 4 and 5) and the resorts of Caucasian mineral waters (CMW) related to cities with prosperous ES (category 1) have been collected and calculated. The following conclusions have been obtained: among the cities analyzed by the degree of ecological trouble the only Zheleznovodsk and Essentuki can be referred to the territories with the tense situation, the rest of the city, including the resort of Kislovodsk can be refered to the territories with critical ecological situation. An integral assessment of the health status of the population of large industrial centers and resorts in the CMW corresponds to the critical environmental situation. The reason is the high population density and the cities layout promoting the accumulation of pollutants in the environment and the formation of the buffer fields of environmental and geochemical contamination of federal resorts.